Effect of Project-Based Learning on Vocational High School Student’s Cognitive and Psychomotor Competencies in CAD - Hendry Rahmad Hidayat; Widiyanti Widiyanti (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
This study investigates the effect of Project-Based Learning (PjBL) on students’ cognitive understanding and psychomotor performance in the Computer Aided Design (CAD) subject, a core course within the Mechanical Engineering program at SMKN 1 Singosari. The research was motivated by the need to bridge the gap between theoretical instruction and real-world design competencies in vocational education. A quantitative descriptive approach was employed, with a total sampling technique involving all students enrolled in the CAD course during the ongoing semester. Data were collected through cognitive tests, practical performance assessments, and Likert-scale questionnaires to measure perceptions. The results revealed that students achieved high levels of cognitive mastery, with dominant correct responses on key CAD concepts such as part modeling, assembly environments, and technical file formats. Psychomotor evaluations indicated consistent practical performance, with a mean score of 82.36, while perception analysis reflected high levels of student engagement and satisfaction with the PjBL model. These findings suggest that PjBL effectively fosters integrated learning experiences that enhance technical understanding, practical skills, and student motivation. Consequently, the adoption of project-based strategies is recommended for vocational curricula to support competency-based education in technical fields.